2016
DOI: 10.1089/jmf.2015.0075
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Intake of Sesame Seeds (Sesamum indicum L.) and Derivatives on Oxidative Stress: A Systematic Review

Abstract: This study is aimed at assessing the scientific evidence on the effect of the intake of sesame seeds and derivatives on oxidative stress of individuals with systemic hypertension, dyslipidemia, and type 2 diabetes mellitus. A systematic review was conducted in seven databases (Lilacs, PubMed, ISI Web of Knowledge, Cochrane Library, Scopus, Trip Database, and Scielo) from September 2013 to January 2014. Clinical trials on the intake of sesame seeds and derivatives assessing the outcomes related to oxidative str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(16 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…Thus, chia has a high concentration of polyphenols derived from caffeic acid and other antioxidant substances [ 13 , 14 , 16 , 17 ]. The antioxidant potential of flax [ 18 ], sesame [ 19 , 20 ], pumpkin [ 7 ] and sunflower seeds [ 21 ] has also been highlighted. In the case of chia and flax seeds, it has been demonstrated that the partial germination of the grains can increase both their antioxidant capacity and the content of phenolic compounds [ 22 ].…”
Section: Nutritional Profilementioning
confidence: 99%
“…Thus, chia has a high concentration of polyphenols derived from caffeic acid and other antioxidant substances [ 13 , 14 , 16 , 17 ]. The antioxidant potential of flax [ 18 ], sesame [ 19 , 20 ], pumpkin [ 7 ] and sunflower seeds [ 21 ] has also been highlighted. In the case of chia and flax seeds, it has been demonstrated that the partial germination of the grains can increase both their antioxidant capacity and the content of phenolic compounds [ 22 ].…”
Section: Nutritional Profilementioning
confidence: 99%
“…Sesame oil is composed of lignans (sesamin, sesamolin), minerals, vitamins, phytosterols, unsaturated fatty acids (linoleic acid, oleic acid, etc) and tocopherols (142)(143)(144). Many studies have shown that sesame oil has antioxidant, antihypertensive, antihyperlipidemic, antihyperglycemic, anticarcinogenic and immunoregulatory activities (145)(146)(147)(148). Diabetes patients may prefer sesame oil as it reduces the detrimental effects of diabetes by improving glucose control, blood pressure, lipid levels and cardiac and renal health (149)(150)(151)(152).…”
Section: Aloe Vera (Aloe Barbadensis Miller)mentioning
confidence: 99%
“…Thus, sesame oil may be associated with the improvement of oxidative stress as shown by some scientific evidence [8]. Guinaz et al (2009) analyzed the vitamin E content in vegetable oils and observed that canola oil had the highest alpha-tocopherol content (18.39 mg / 100 mL) when compared to soybean oil (12.14 mg / 100 mL) and extra-virgin olive oil (14.05 mg / 100 mL) [37].…”
Section: Copyright: © 2017 Egbuonu and Orijimentioning
confidence: 99%
“…It is known that there is a great influence in relation to its ingestion and quantity of the fatty acids on the health, mainly, in relation to the cardiovascular diseases [6], which are considered the main cause of death in the world, around 37% [7]. Scientific evidence indicates that the increase in the consumption of unsaturated fatty acids present, for example, in vegetable oils is effective in preventing these diseases [8,9]. The combination of the beneficial fatty acid profile and the rich nutritional composition of the sesame oil makes it possible to be considered a quality food with excellent functional properties.…”
Section: Introductionmentioning
confidence: 99%